Water Quality of Sundarijal Reservior and its Feeding Streams in Kathmandu - Bhattarai, Krishna R; Shrestha, Bharat B; Lekhak, Hari D (Scientific World, 2010)
Physico-chemical (pH, conductivity, dissolved oxygen, alkalinity, hardness, nitrogen, heavy metal, etc) and bacteriological (coliform bacteria) characteristics of water were studied in samples collected from Sundarijal reservoir and its main feeding streams: Bagmati, Nagmati and Shyalmati in 2003 and 2004 AD. Human activities near the water bodies and sanitary condition of the residential areas of watershed were also examined. Although public awareness and proper management of watershed and reservoir premises were lacking, yet the physico-chemical characters were within the standard of World Health Organization (WHO) and European Commission (EC) for drinking water. However, the coliform bacteria were high and water was not safe to consume without intense treatments with disinfectants. Key words: Coliform; Heavy metals; Human activities; Physico-chemical characters; Sanitary condition. DOI: 10.3126/sw.v6i6.2643 Scientific World, Vol. 6, No. 6, July 2008 99-106